Continuously Stirred Tank Reactor for Pharmaceutical and Chemical Applications - Junhua Li; Yibo Zhou; Hanqi Zhou; Fengfan Liu; Fuli Zhang (Pharmaceutical Fronts)
In the fields of drug synthesis and fine chemicals, the traditional kettle-type reactor with a small heat exchange area and the microreactor which is easy to clog, are not suitable for the reaction with fast reaction speed, large heat release, and high solid content. However, the continuously stirred reactor has the advantages of high mass and heat transfer efficiency, high reaction safety, and not easy to be clogged, and therefore, has a great potential for application. This paper reviews the research progress of continuous agitation reactors in organic synthesis, drug crystallization, and biocatalysis, hoping to provide a reference for applications of continuous agitation reactors in the pharmaceutical and chemical fields.